Long-lived positive parity isomer in 76Br - Kreiner, A. J.; García Bermúdez, G.; Mariscotti, M. A. J.; Thieberger, P. (Elsevier B.V., 1979)
Fil: Kreiner, A. J. Comisión Nacional de Energía Atómica; Argentina